2017
DOI: 10.1111/jvec.12262
|View full text |Cite
|
Sign up to set email alerts
|

Wing morphology variations in a natural population ofPhlebotomus tobbiAdler and Theodor 1930

Abstract: Cutaneous leishmaniasis (CL) is highly endemic in the Cukurova region, located on the crossroads of main refugee routes from the Middle East to Europe on the eastern Mediterranean part of Turkey. Our purpose was to investigate the phenotypic variation of Phlebotomus tobbi, the known vector of CL in the region, during one active season. Sand flies and microclimatic data were collected monthly from May to October, 2011, from five locations in six villages in the study area. A geometric morphometric approach was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The thin-plate spline analyses showed that most of the shape changes (landmark movements) occurred on the radial (landmarks 11, 12, 13, 14 and 15) and medial (2, 3, 7, 8, 9 and 10) portions of the S. calcitrans wing. Oguz et al [56] observed the same variation in the radial portion of the wing of Phlebotomus tobbi Adler & Theodore. Pieterse et al [59] found variation in wing landmarks located at the costal, sub-costal and radial veins of Bactrocera dorsalis (Hendel) and Ceratitis capitata (Wiedemann) reared from nectarine, plum, pear and apple.…”
Section: Discussionmentioning
confidence: 71%
“…The thin-plate spline analyses showed that most of the shape changes (landmark movements) occurred on the radial (landmarks 11, 12, 13, 14 and 15) and medial (2, 3, 7, 8, 9 and 10) portions of the S. calcitrans wing. Oguz et al [56] observed the same variation in the radial portion of the wing of Phlebotomus tobbi Adler & Theodore. Pieterse et al [59] found variation in wing landmarks located at the costal, sub-costal and radial veins of Bactrocera dorsalis (Hendel) and Ceratitis capitata (Wiedemann) reared from nectarine, plum, pear and apple.…”
Section: Discussionmentioning
confidence: 71%
“…A similar pattern was observed in the way Phlebotomus tobbi (Diptera) responded to temperature. In the case of this species, the wing size of females correlated negatively with temperature, while the opposite was true for males [30]. Studies on the metric features of the ground beetle Carabus granatus have indicated variations in body length dependent on locality in the geographic range, level of anthropogenic influence and degree of biotope openness in the Eurasia region [31].…”
Section: Discussionmentioning
confidence: 99%
“…The membranous wings in insects (the hindwings in Coleopterans) are particularly well suited for GM; their two‐dimensional shape reduces possible distortions due to angle and depth‐of‐field that are possible with 3‐dimensional subjects when photographed (Webster and Sheets 2010), and they possess numerous suitable LMs at the terminations and intersections of veins. Membranous wings have been shown to be a particularly useful feature for identifying morphological variation among insect populations (Oguz et al 2017, Wilk‐da‐Silva et al 2018).…”
Section: Methodsmentioning
confidence: 99%